OPTIMASI PENGGUNAAN HIDROKOLOID TERHADAP PASTA MAKARONI BERBASIS BERAS BERAMILOSA TINGGI - Eko Hari Purnomo; Endang Yuli Purwani; Tri Wahyu Sulistyawati (Jurnal Teknologi dan Industri Pangan, 2015)
Pasta is an extrusion product which is commonly produced from wheat flour. Gluten is key substance of wheat flour that affect quality of pasta, such as low cooking loss, low adhesiveness and firm pasta structure. However, gluten may cause health problem for consumers with celiac disease or gluten intolerance. Rice is safe for celiac disease sufferer, but it is technologically challenging to develop rice-based pasta. The objective of this research was to evaluate the effect of different ratio between xanthan gum and guar gum (2%) on the physical characteristics of macaroni pasta from rice flour. This research consisted of several steps which include flour milling and characterization, formulation, and final product analysis. The result showed that different ratio of xanthan gum and guar gum had significant effect to cooking loss, adhesiveness, springiness and hue parameters (P<0.05), but it did not give significant effect to water absorbtion, swelling volume, chroma and lightness response (P>0.05). The optimum formula was noodle by hydrocolloid ratio 2% of xanthan gum and 0 % of guar gum which had desirability value of 0.798. The selected formula was organoleptically accepted by panelists and containing 9.84 % of water, 1.65% of ash, 12.05% of protein, 1.41% of fat, 75.05% of carbohydrate, 24.49% of amylose, also 33.49  of pore size.